Engineering CAR-T Cells for Improved Function Against Solid Tumors - Morgan, Michael A.; Schambach, Axel (Frontiers in Immunology, 2018)
Genetic engineering T cells to create clinically applied chimeric antigen receptor (CAR) T cells has led to improved patient outcomes for some forms of hematopoietic malignancies. While this has inspired the biomedical community to develop similar strategies to treat solid tumor patients, challenges such as the immunosuppressive character of the tumor microenvironment, CAR-T cell persistence and trafficking to the tumor seem to limit CAR-T cell efficacy in solid cancers. This review provides an overview of mechanisms that tumors exploit to evade eradication by CAR-T cells as well as emerging approaches that incorporate genetic engineering technologies to improve CAR-T cell activity against solid tumors.